Irregular Spatial Distributions of Spectral Line Parameters in the Middle Solar Chromosphere Revealed from Analysis of Solar Flash Mg ib2 Spectra. (1st August 2022) - Jin, Yuhang; Qu, Zhongquan; Xu, Zhi; Dun, Guangtao; Chang, Liang; Cheng, Xiangming; Zhang, Xiaoyu; Deng, Linhua; Peng, Yang
Abstract: This paper presents the analytical results of solar Mg i b 2 flash spectra, obtained by the prototype Fiber Arrayed Solar Optic Telescope in process of the 2013 Gabon total solar eclipse. The analysis reveals irregular distributions of the spectral line parameters like ratio of line source function to continuum one β, ratio of line emissivity to continuum emissivity ζ, ratio of the continuum opacity to the line opacity r 0, line center optical depth τ 0, the line width Δ λ D, and the line-of-sight velocity v los, while the approximately spherical symmetry can be found in the maps of integrated line intensity and continuum intensity. These irregular distributions originate from those of line profile features like the maximum intensity, the line width and line center wavelength. It is also found from the recovered line center optical depth τ 0 that in the middle chromosphere, the optical depth is not small due to non-ignorable absorption and the long light path along the line-of-sight. Finally, we show that the excessive broadening of spectral lines can be due to co-existence of multiple radiative sources with different line-of-sight velocities unresolved in one detector pixel.